Pelatihan Bahasa Inggris untuk Anak Usia Dini dengan Fun English: English Training for Children using Fun English - Wedhowerti Wedhowerti; Almira Ghassani Shabrina Romala; Harris Hermansyah Setiajid; Simon Arsa Manggala; Epata Puji Astuti; Catharina Brameswari; Diksita Galuh Nirwinastu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The people of Nologaten RT 10 RW 04 needed help, especially regarding English. This is due to parents' lack of knowledge and education levels, so they could only guide their children with minimal access to effective learning materials for learners at an early age. Learning English from an early age is necessary so that in its later development, learners will easily master English. English Letters Department of Universitas Sanata Dharma designed a community service activity, i.e., English Training for Children at Nologaten RT 10 RW 04. The series of community service activities began in February 2022 to recruit volunteers. Then the program's implementation started in July 2022 and ended in August 2022; this community service activity is expected to further strengthen the image of Universitas Sanata Dharma as a university that is concerned with the interests of the community in general and will further enhance the 3C spirit (competence, conscience, compassion) among lecturers and student volunteers, as well as to make English Letters Department of Universitas Sanata Dharma give positive impact to society. The post-test results yield increasing scores of 28% compared to the previous pre-test in all three evaluation domains (cognitive, affective, and psychomotor). They are also interested in listening to others while speaking, showing good cooperation with other group members, starting a simple English conversation, and asking questions in correct grammar.